Revealing 21 per cent of GDP in hidden assets: Evidence from Argentina's tax amnesties - Juliana Londo\~no Vélez; Dario Tortarolo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper studies the effectiveness of tax amnesties and their impacts on capital taxation and public spending. We leverage rich policy variation from Argentina, where left- and right-wing governments implemented multiple programmes and achieved varying success. After numerous failed enforcement efforts, its 2016 scheme reportedly revealed assets worth 21 per cent of GDP-the world's most successful tax amnesty. We use detailed data from fiscal tabulations spanning two decades and obtain three key results. First, despite substantial offshore tax evasion, declared foreign assets quadrupled after the 2016 amnesty. Second, disclosures were extensive among the wealthiest 0.1 per cent of individuals, who more than doubled their declared assets. Third, improving tax compliance has sizeable fiscal externalities on capital taxes and social transfers: the wealth and capital income tax bases more than doubled, and the amnesty's earmarked revenue boosted pension benefits by 15 per cent. We conclude by discussing the lessons from Argentina's experience with amnesty programmes.
Keywords: D31; H26; H31; 330; tax evasion; amnesties; enforcement; Argentina